Inhibition of Metastatic Spread by I.C.R.F. 159: Selective Deletion of a Malignant Characteristic. Issue 5731 (7th November 1970) - Salsbury, A. J.; Burrage, Karen; Hellmann, K.
Abstract : Treatment with I.C.R.F. 159 completely inhibited metastasis formation in mice implanted with Lewis lung carcinoma at doses having little influence on the rate of growth of the primary implant. This inhibition was due to the effect of I.C.R.F. 159 on the development of blood vessels of the invading margins of the primary tumour. So far as is known, this is the first time a drug has induced a specific loss of the malignant characteristic of blood-borne tumour cell dissemination.